HYPERTENSION AND CARDIOVASCULAR DISEASES ARE ONE OF THE MAIN RISKS FOR STOMATOLOGISTS PRACTICING IN RURAL COUNTIES - original study- - Celina Silvia Stafie; Cristian Sorin Prepeliuc; Dan Alexandru Costache; Stefania Teodora Duca (Romanian Society of Oral Rehabilitation, 2021)
Introduction: The overall risk of dental procedures should be rigorously assessed, including the cumulative risk of latex contamination (gloves, instruments, operating fields), local anesthesia, composite materials and in addition the patient's personal risk (cardiovascular). Material and methods: the study was retrospective and was performed in a rural community, respectively Pătrăuți locality, Suceava county. Data were collected on the factors that characterize the lifestyle and working conditions of the analyzed population, heredo - collateral and personal history, anthropometric data, biochemical parameters( lipid profile, glycemia and glycated hemoglobin, BP, presence of obesity and diabetes type 2, as well as data on dental allergic risk. Results: the prevalence of hypertensive patients among the general population was 14.79% ; Adult patients diagnosed with hypertension are 34.48% male (140 patients) and 65.52% female (266 patients), the prevalence of hypertension among the adult population being 8.09% for men and 18.38% for women. Conclusions: Hypertension was a common risk factor in the study population, which raised the additional risk profile in the dental office, especially among the Roma population, decreasing the addressability to the office.